(untitled) (World Bulletin of Public Health, 2025)
Determination of homocysteine levels is important in clinical practice, as elevated levels are associated with an increased risk of cardiovascular disease, neurological disorders, and other pathologies. Several laboratory methods are available for the determination of homocysteine, including immunochemical methods and high-performance liquid chromatography (HPLC) methods. These methods provide accurate determination of homocysteine, which allows for early detection of diseases